An Analysis on the Usage of Rhetorical Technigues as Appeared in Visuddhimagga - Jampan, Wutthikrai (Mahachula Academic Journal, 2025)
This research article has three objectives: (1) to study the concept of figurative language, (2) to examine the historical background, structure, and content of the Visuddhimagga, and (3) to analyze the stylistic strategies of figurative language found in the Visuddhimagga. This study employs documentary research, drawing on the Visuddhimagga itself and related scholarly works. The findings showed that figurative language functions as a linguistic device that evokes emotion, imagery, and profound meaning, thereby enhancing clarity, aesthetic value, and accessibility in communication. The study identifies nine types of figurative language—simile, metaphor, personification, hyperbole,onom atopoeia, metonymy, irony, symbolism, and litotes. Effective use of these figures of speech must correspond to context in order to evoke imagery and emotions aligned with the intended teachings. In practice, figurative language can be applied to writing, literature, speech, and communication—particularly in Buddhist literature, where it conveys profound doctrines in an accessible manner, and in Thai literature, where it enhances beauty and emotional value. Thus, it is regarded as a vital tool in creative communication, imbuing content with vitality and power. The study further shows that the Visuddhimagga, composed by Buddhaghosa in the 5th century CE, serves as a practical manual for both monks and lay Buddhists. Its structure encompasses the threefold training—morality (sĩla), concentration (samãdhi), and wisdom (paññã)—across 23 chapters. The text systematically explains the cultivation of body, speech, mind, and insight leading to liberation, employing both prose and verse. Hence, the Visuddhimagga has been hailed as the “master manual of practice.”Analysis of figurative language within the text identifies 203 instances, most prominently connected to morality, concentration, and wisdom. Five types—simile, metaphor, irony, hyperbole, and personification—appear most frequently, especially in the section on morality, followed by concentration and wisdom. Their use plays a crucial role in enriching language, stimulating imagination, and simplifying complex ideas. Additionally, the research proposes the R.I.C.E.S. Model as a new conceptual framework for rhetorical communication, consisting of five stages: R – Rhetorical integration, I – Imagery creation, C – Critical thinking stimulation, E – Emotional engagement, and S – Symbolic representation for clarity. This model can be applied to teaching, research, Dhamma dissemination, meditation practice, and digital innovation. In conclusion, the use of figurative language in the Visuddhimagga not only facilitates the transmission of Buddhist doctrines in an accessible and engaging way but also bridges academic research with contemporary communication and spiritual practice. This integration enlivens Buddhism and guides practitioners toward the ultimate goal—liberation.